2019
DOI: 10.1186/s13017-019-0235-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of intrathoracic and cervical anastomotic leakage after esophagectomy for esophageal cancer: a systematic review

Abstract: Background Anastomotic leakage (0–30%) after esophagectomy is a severe complication and is associated with considerable morbidity and mortality. The aim of this study was to determine which treatment for anastomotic leakage after esophagectomy have the best clinical outcome, based on the currently available literature. Methods A systematic literature search was performed in Medline, Embase, and Web of Science until April 2017. All studies reporting on the specific treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 35 publications
2
39
3
4
Order By: Relevance
“…Our anastomotic leaks accounted for 2(4%), of the deaths and had a 2/7 (28 %) mortality which is comparatively higher than a 12 % mortality from anastomotic leak found in a systematic review done by Verstegenet al 28 and other recent data 30 but comparable to the 37 % mortality reported by Turkyilmaz A et al 29 Even though Gockel and colleges 9 in their study involving 424 patients suggested that tumor characteristics, e.g. TNM classi cation, were of no in uence on the postoperative course our study, however, found that N3 stage, hence stage III disease, is signi cantly associated with adverse short term postoperative outcomes (AOR 0.04 (0.01-0.97 p= 0.048).…”
Section: Discussioncontrasting
confidence: 48%
“…Our anastomotic leaks accounted for 2(4%), of the deaths and had a 2/7 (28 %) mortality which is comparatively higher than a 12 % mortality from anastomotic leak found in a systematic review done by Verstegenet al 28 and other recent data 30 but comparable to the 37 % mortality reported by Turkyilmaz A et al 29 Even though Gockel and colleges 9 in their study involving 424 patients suggested that tumor characteristics, e.g. TNM classi cation, were of no in uence on the postoperative course our study, however, found that N3 stage, hence stage III disease, is signi cantly associated with adverse short term postoperative outcomes (AOR 0.04 (0.01-0.97 p= 0.048).…”
Section: Discussioncontrasting
confidence: 48%
“…Our anastomotic leaks accounted for 2(33.3%),of the deaths and had a 2/7 (28.5 %) mortality which is comparatively higher than a 12 % mortality from anastomotic leak found in a systematic review done by Verstegenet al 28 and other recent data 30 but comparable to the 37 % mortality reported by Turkyilmaz A et al 29 Even though Gockel and colleges 9 in their study involving 424 patients suggested that tumor characteristics, e.g. TNM classi cation, were of no in uence on the postoperative course our study ,however, found that N3 stage, hence stage III disease, is signi cantly associated with adverse short term postoperative out comes (AOR 0.04 (0.01-0.97 p= 0.048) .…”
Section: Discussioncontrasting
confidence: 47%
“…Our anastomotic leaks accounted for 2(4%), of the deaths and had a 2/7 (28 %) mortality which is comparatively higher than a 12 % mortality from anastomotic leak found in a systematic review done by Verstegenet al 28 and other recent data 30 but comparable to the 37 % mortality reported by Turkyilmaz A et al 29 In 3 cases there was part of a tumor leftover as it was deemed dangerous to proceed with complete tumor removal due to the T4b stage of the tumor. These were not avoided from pre-operative work due to a combination of pre-operative radiologic imaging's' failure to properly identify the stage of the tumor, the fact that there are very few oncologic units which are overwhelmed by oncologic patients and the lack of esophageal stenting for palliation.…”
Section: Intrathoracic Anastomosiscontrasting
confidence: 48%